Characterisation of HIV-1 molecular transmission clusters among newly diagnosed individuals infected with non-B subtypes in Italy. (10th May 2019) - Fabeni, Lavinia; Alteri, Claudia; Berno, Giulia; Scutari, Rossana; Orchi, Nicoletta; De Carli, Gabriella; Bertoli, Ada; Carioti, Luca; Gori, Caterina; Forbici, Federica; Salpini, Romina; Vergori, Alessandra; et al.
Abstract : Objective: We evaluated the characteristics of HIV-1 molecular transmission clusters (MTCs) in 1890 newly diagnosed individuals infected with non-B subtypes between 2005 and 2017 in Italy. Methods: Phylogenetic analyses were performed on pol sequences to characterise subtypes/circulating recombinant forms and identify MTCs. MTCs were divided into small (SMTCs, 2–3 sequences), medium (MMTCs, 4–9 sequences) and large (LMTCs, ≥10 sequences). Factors associated with MTCs were evaluated using logistic regression analysis. Results: 145 MTCs were identified and involved 666 individuals (35.2%); 319 of them (16.9%) were included in 13 LMTCs, 111 (5.9%) in 20 MMTCs and 236 (12.5%) in 112 SMTCs. Compared with individuals out of MTCs, individuals involved in MTCs were prevalently Italian (72.7% vs 30.9%, p<0.001), male (82.9% vs 62.3%, p<0.001) and men who have sex with men (MSM) (43.5% vs 14.5%, p<0.001). Individuals in MTCs were also younger (median (IQR) years: 41 (35–49) vs 43 (36–51), p<0.001) and had higher CD4 cell count in comparison with individuals out of MTCs (median (IQR): 10 9 /L: 0.4 (0.265–0.587) vs 0.246 (0.082–0.417), p<0.001). The viral load remained stable between the two groups (median (IQR) log10 copies/mL: 4.8 (4.2–5.5) vs 5.0 (4.3–5.5), p=0.87). Logistic regression confirmed that certain factors such as being MSM, of Italian origin, younger age and higher CD4 cell count were significantly associated with MTCs. Conclusions: Our findings show that HIV-1 newly diagnosed individuals infected with non-B subtypes are involved in several MTCs in Italy. These MTCs include mainly Italians and MSM and highlight the complex phenomenon characterising the HIV-1 spread. This is important especially in view of monitoring the HIV epidemic and guiding the public health response.